2021
DOI: 10.1038/s41598-021-96492-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of IMP3 and p53 immunohistochemical staining in EUS-guided fine-needle aspiration for solid pancreatic tumors

Abstract: We previously identified insulin-like growth factor-II messenger ribonucleic acid-binding protein 3 (IMP3) as a valuable marker to distinguish malignant from benign lesions in pancreatic solid masses. The aim of this prospective study was to evaluate the usefulness of IMP3 and p53 immunohistochemical staining in endoscopic ultrasound-guided fine-needle aspiration (EUS–FNA) samples for pancreatic solid masses. The study recruited 90 consecutive patients with pancreatic masses, including 62 pancreatic ductal ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We found diagnostic sensitivity to be lower than that previously reported, probably because we did not perform ROSE or macroscopic on-site evaluation (MOSE). 10,11,[25][26][27][28] However, the majority of reported studies have been conducted by clinicians, and there exists little detailed information regarding PDAC as diagnosed by pathologists on the basis of EUS-FNAC and EUS-FNAB.…”
Section: Discussionmentioning
confidence: 99%
“…We found diagnostic sensitivity to be lower than that previously reported, probably because we did not perform ROSE or macroscopic on-site evaluation (MOSE). 10,11,[25][26][27][28] However, the majority of reported studies have been conducted by clinicians, and there exists little detailed information regarding PDAC as diagnosed by pathologists on the basis of EUS-FNAC and EUS-FNAB.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with cytohistology alone, cytohistological analysis combined with IMP3 staining had substantially higher diagnostic sensitivity, specificity, and accuracy in endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) samples 85 . Tadic et al and Mikata et al also confirmed these findings 90,91 …”
Section: M6a Modification and Diagnosis Of Pcmentioning
confidence: 92%
“…In EUS‐FNA samples, IMP3 staining remarkably improves diagnostic sensitivity, specificity, and accuracy of cytohistological analysis of PDAC, facilitating the distinction between PDAC and benign pancreatic diseases. 91 Moreover, rs9939609 and rs7495G are FTO polymorphism and hnRNP polymorphism, respectively. Both rs9939609 and rs7495G are linked to PC risk, manifesting their potential in PC early diagnosis.…”
Section: M6a Modification and Diagnosis Of Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive classification was inferred when the nucleus or cytoplasm of tumor cells above the cut off value (%) was stained ( Figure 2 ). With reference to past literature [ 21 , 22 , 23 ], p53 staining was inferred as positive when 60% or more of the tumor cell nuclei was stained. Sensitivity and specificity were analyzed for (1) the samples with only p53 staining, (2) only maspin staining, and (3) p53 staining + maspin staining (the test was considered positive if any marker was positive).…”
Section: Methodsmentioning
confidence: 99%